2014
DOI: 10.17711/sm.0185-3325.2014.025
|View full text |Cite
|
Sign up to set email alerts
|

Restauración psicológica y naturaleza urbana: algunas implicaciones para la salud mental

Abstract: SUMMARYTopics relating to mental health promotion systematically lack research that documents the importance of physical environment qualities in the development of public health policies. At the present time, several emerging research lines regarding restorative environments (RE) and psychological restoration (PR) may contribute to the conceptual and operational definition of relevant environmental qualities promoting mental health. PR relates to the recovery of people´s cognitive resources and psychophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
0
27
0
5
Order By: Relevance
“…Mental fatigue and stress-related mental disorders, depression, and anxiety are related to individual mental health and wellknown risk factors for positive mental health (1)(2)(3). One in every four people suffer from mental disorders in their lifetime (1).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mental fatigue and stress-related mental disorders, depression, and anxiety are related to individual mental health and wellknown risk factors for positive mental health (1)(2)(3). One in every four people suffer from mental disorders in their lifetime (1).…”
Section: Introductionmentioning
confidence: 99%
“…Mental fatigue and stress-related mental disorders, depression, and anxiety are related to individual mental health and wellknown risk factors for positive mental health (1)(2)(3). One in every four people suffer from mental disorders in their lifetime (1). Environmental health related researchers have suggested that green environments can reduce levels of stress related mental disorders and therefore enhance positive mental health (2,(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations

Ecospirituality and Health: A Systematic Review

de Diego‑Cordero,
Martínez-Herrera,
Coheña-Jiménez
et al. 2024
J Relig Health